Effects of nitrogen fertilizer and biochar levels on soil CO2 emission and wheat yield in irrigation region - Yang, Weijun; Zhang, Liyue; Chen, Yuxin; Su, Lili; Zhao, Lining; Li, Pengying; Zhao, Hongmei; Jia, Hongtao (Frontiers in Agronomy, 2024)
IntroductionThis study examined the impact of biochar application on agricultural productivity and greenhouse gas emissions in irrigated regions of northern Xinjiang. The objective of this study was to assess the impact of nitrogen fertilizer and biochar levels on soil respiration rate, enzyme activity, and spring wheat yield.Materials and methodsThe experiment employed a randomized block design comprising two nitrogen fertilizer levels (N1: 300 kg·hm-2 and N2: 255 kg·hm-2) and four biochar levels (B0: 0 kg·hm-2, B1: 10×103 kg·hm-2, B2: 20×103 kg·hm-2, and B3: 30×103 kg·hm-2). This resulted in eight groups (N1B0, N1B1, N1B2, N1B3, N2B0, N2B1, N2B2, and N2B3), each replicated three times.Results and discussionThe findings indicated that the N2B2 group exhibited a reduction in soil CO2 emissions, with a cumulative decrease of 4.42% in CO2 emissions compared to the N2B0 control. The application of biochar and/or nitrogen fertilizer, particularly in combination, was observed to increase soil urease, sucrase, and catalase activities. The N2B2 group exhibited a spring wheat yield of 8301.35 kg·hm-2, representing a 22.1% increase over the N1B0 group. This improvement was attributed to the capacity of biochar to regulate soil water content variability, stabilize soil aggregate composition, mitigate organic carbon mineralization, and reduce farmland carbon emissions. Furthermore, biochar’s nitrogen fixation provided essential nutrients for soil microorganisms, thereby enhancing enzymatic reactions and promoting crop growth.ConclusionIn conclusion, the N2B2 regime was determined to be the optimal approach for spring wheat cultivation in irrigated regions of northern Xinjiang, resulting in enhanced crop productivity and the mitigation of carbon emissions. Nevertheless, further investigation of its long-term impact on farmland is recommended.